2014
DOI: 10.1021/nn500454n
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Platform for Hyperthermia Application in Cancer Treatment: Cobalt-Doped Ferrite Nanoparticles Mineralized in Human Ferritin Cages

Abstract: Magnetic nanoparticles, MNPs, mineralized within a human ferritin protein cage, HFt, can represent an appealing platform to realize smart therapeutic agents for cancer treatment by drug delivery and magnetic fluid hyperthermia, MFH. However, the constraint imposed by the inner diameter of the protein shell (ca. 8 nm) prevents its use as heat mediator in MFH when the MNPs comprise pure iron oxide. In this contribution, we demonstrate how this limitation can be overcome through the controlled doping of the core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(123 citation statements)
references
References 68 publications
2
121
0
Order By: Relevance
“…No variation in the line broadening between samples was observed that indicated that the addition of cobalt did not affect the crystallinity or particle size as has been observed in some other cases using traditional solution synthesis of other ferritins 13,14 . This was consistent with the previously observed characteristics of PfFt in providing a favourable environment for the efficient formation of well crystallized nanoparticles 10 , and facilitates a comparison of the intrinsic magnetism.…”
Section: A Overall Structure and Compositionmentioning
confidence: 55%
“…No variation in the line broadening between samples was observed that indicated that the addition of cobalt did not affect the crystallinity or particle size as has been observed in some other cases using traditional solution synthesis of other ferritins 13,14 . This was consistent with the previously observed characteristics of PfFt in providing a favourable environment for the efficient formation of well crystallized nanoparticles 10 , and facilitates a comparison of the intrinsic magnetism.…”
Section: A Overall Structure and Compositionmentioning
confidence: 55%
“…[61][62][63] In recent years, attempts have been made to enhance their properties and to impart unique functionalities to these nanomaterials by employing surface-initiated NCA polymerization. Yang and co-workers prepared magnetic-silica polypeptide hybrids by polymerizing NCA-BLG from the nanoparticle surface.…”
Section: Research Newsmentioning
confidence: 99%
“…The N-termini of the subunits are positioned on the external protein surface near the threefold axis, which is a very suitable position to introduce additional functionalities such as for mineralization, 42,43) crystallization, 44,45) and cell recognition. 40,46,47) The C-termini point towards the cavity on the fourfold symmetry axis and can be used to generate nucleation points for mineral growth. 48) Mutations in the ferroxidase catalytic centers and at the nucleation sites have been generated to study iron metabolism.…”
Section: Structures and Assemblymentioning
confidence: 99%
“…For example, magnetic Fe 3 O 4 75) 41,[84][85][86][87] for magnetic resonance imaging, 32,46) and even as the core of a magnonic device. 88) In analogy, Co(O)OH 89) 91) Many metal hydroxide NPs can be grown from the respective metal ion without an oxidizer.…”
Section: Apoferritinmentioning
confidence: 99%